Improving student life with EZ.B shoe dryer - Che Zalman, Muhammad Zaquan Hakimi; Md Romy, Nor Ain; Farid Redza, Ainin Sofea; Porvito, Farah Athirah; Norhizam, Nur Amani Zahirah; Mohammad, Noorita (Universiti Teknologi MARA, Negeri Sembilan, 2025)
In the monsoon season, people have trouble drying their shoes. Additionally, most people dry their shoes under a fan or behind a fridge. Some people stuff and stuff their shoes with newspaper. Users, especially students, expect the new shoe dryer machine to solve this problem quickly. Students' daily lives inspired our idea. According to brief interviews and questionnaires, many Generation Z students have multiple pairs of trainers and prefer shoes over sandals. They sweat and stink their shoes, especially if they play sports or outdoors. We introduce EZ.B then. Our invention's prototype is a compact shoe rack that holds 2–4 pairs. It quickly and uniformly dries shoes and reduces odour. Despite its size and cost, it is ideal for dormitories and family homes where multiple students can use it. Based on student needs and challenges, this project introduces a new product concept. EZ.B is practical, convenient, and has great potential, especially among young, eager customers.